Thymoquinone Attenuates Immune Mediated Liver Injury Induced by Concanavalin A in Mice - Ahmad, Halla A.; H. Kathem, Sarmed (Iraqi Journal of Pharmaceutical Sciences, 2021)
Autoimmune hepatitis is an inflammatory disease and its incidence has been increasing. The features of hepatitis are the release of inflammatory cytokines, the elevation of AST and ALT, and hepatocyte apoptosis and necrosis. Concanavalin A considered as essential model represents the acute immune-mediated liver damage in rodents. Thymoquinone is well known herbal compound that exert hepatoprotective, anti-inflammatory, and antioxidant activity. In this study, we focus on the immunoregulatory and liver protective effect of thymoquinone in a mouse model of concanavalin A-induced liver injury.Twenty-four male mice were randomly divided into four groups each containing six animals: Negative control group, concanavalin A model group, thymoquinone 15mg/kg group, and thymoquinone 30mg/kg group. Blood was collected to detect the activities of alanine transaminase (ALT) and aspartate transaminase (AST) as well as liver tissue for the detection of tumor necrosis factor levels, after 8 hours of concanavalin A injection.Injecting mice with concanavalin resulted in a dramatic increase in serum level of both ALT and AST which indicate severe liver tissue damage with a significant increase in inflammatory cytokines TNF alpha -and INF levels, with a notable increase in NF-kB gene expression in mice liver tissue homogenate. Thymoquinone pretreatment revealed a dose-dependent increase in liver tissue protection.Conclusion: Thymoquinone has hepatoprotective and immune modulatory effects in concanavalin A induced immune mediated liver damage. Thymoquinone exerted its effect through attenuating NF and its downstream effectors TNF and INF in a dose dependent manner.